PLANNING OF THE CHECK DAM OF JACOBUS RED ROAD–AMBON CITY : Perencanaan Pemeriksaan Dam Jacobus Jalan Merah – kota Ambon - Assagaf, Sjaid S Fais; Kubangun, Hamdani (Uniqbu Journal of Exact Sciences, 2021)
Ambon city, which mostly consists of hilly areas, is an area that is very highly susceptible to the occurrence of debris mass movements, both in the form of debris flows and landslides (debris flows, erosions, and slope failures). In the city of Ambon, rivers are passed such as Way Ruhu, Way Batu Merah, Way Tantui, Way Tomu, Way Batu Gajah and Way Batu Hang. The purpose of this paper is to plan the check dam building for Way Batu Merah – Ambon City. The method used is Hydrological Analysis: hydrology as the basis for planning the Q25 Check Dam Building, which consists of rainfall analysis and the basis for calculating the planned discharge used in planning, using the Sabo Technical Center method. From the calculation results, it is obtained that the planned Q25 flood discharge of the Way Batu Merah River is 516.43 m / year with a return period of 25 years, the sediment volume can be accommodated 22,102 m / year and controlled by the Check Dam 56,050 m / year, then with a sediment discharge of 60,685 m³ / year . By comparing the amount of sediment that enters the Check Dam with the capacity of the Check Dam, it is dredged again for 3.5 years. Keywords: Sediment; Hydrological Analysis; Checkdam; Sediment Discharge